Harmoni Digital dalam Keuangan Islam: Tinjauan Pustaka Tentang Kepatuhan Syariah dan Integrasi Teknologi - Samsul Arifin; Mustofa; Silvia Rachmawati; Fatimatus Zahroh (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Digital transformation in the Islamic finance sector provides opportunities to improve financial efficiency and inclusion, but also faces complex challenges in maintaining Shariah compliance and integrating technology in line with Islamic ethical principles. This study aims to analyse the linkages between digitalisation and Shariah compliance, and identify challenges and opportunities in the integration of technology into the Islamic financial system. Using a qualitative research method based on library research, this study analyses selected literature from the Google Scholar database through a thematic approach. The results show that technologies such as blockchain, artificial intelligence (AI), and smart contracts have the potential to improve transparency and accountability, but their effectiveness is highly dependent on the design of the system in accordance with maqasid al-shariah. Key challenges include cybersecurity risks, global regulatory misalignment, and cultural resistance caused by low digital literacy. On the other hand, innovations in Islamic fintech and Shariah-based crowdfunding provide opportunities to expand access to inclusive finance. The implications of this study emphasise the importance of an adaptive regulatory framework, cross-disciplinary collaboration (including technologists, scholars, and regulators), and human resource capacity building to ensure alignment between sharia principles and technological developments. The findings provide a foundation for the development of sustainable Islamic finance policies and practices in the digital era.